Rare genetic variants in patients with cervical artery dissection: $hChristopher Traenka, Manja Kloss, Tim Strom, Philippe Lyrer, Tobias Brandt, Leo H. Bonati, Caspar Grond-Ginsbach and Stefan Engelter - Tränka, Christopher; Kloss, Manja; Grond-Ginsbach, Caspar (European stroke journal, 2019)
The potential role of genetic alterations in cervical artery dissection (CeAD) pathogenesis is poorly understood. We aimed to identify pathogenic genetic variants associated with cervic...
Gesehen am 17.04.2020